O abismo como espelho: formas e efeitos da metaficção em O assassino cego (2000), de Margaret Atwood - Quintiere, Isabor Meneses (2021)
The objective of this work is to analyze the novel The blind assassin (2000), by Margaret Atwood, focusing on its metafictional aspects and observing the articulation between metafiction and character subjectivity in its multiple diegetic levels. In order to do so, there is a first chapter on the concepts of metafiction and mise en abyme, applying the theories of Gass (1980), Dällenbach (1980), Ron (1987), Waugh (2001), Bernardo (2010) and Hutcheon;and on subjectivity in fiction, through the theories of Lodge (1992), Culler (1999), Candido (2009), Wood (2012) and Todorov (2013). The writings of Genette (2010) and Rajewsky (2012) are also applied when discussing the intermediality present in the novel. The second chapter analyzes metafiction as the foundation of Atwood’s work, taking into consideration four main points of the narrative and separating them by levels. The results obtained through this analysis show that the metafictional devices are used to compose the characters’ fragmentation, presenting metafiction from a perspective that is not only formalist but also filled with subjectivity and sociopolitical criticism. This work also adds to the pre-existing theory on this corpus, considering that other works have given less importance to its aesthetic composition by focusing mainly on discussions of feminism and gender, while the present one focuses on the novel’s articulation between experience and form.